Incidência de desfechos desfavoráveis e scores de gravidade de pacientes em Unidade de Terapia Intensiva com e sem diagnóstico de COVID-19: estudo de caso-controle - Vasconcelos, Jéssika Barros Dantas (2023)
Introduction: The Intensive Care Unit (ICU) is a place dedicated to the care of critical patients, where the objective is to have a structure capable of providing what is necessary for highly complex care. With the COVID-19 pandemic, there was an exponential need for beds, as a portion of these patients evolve with greater severity. ICU management is linked to identifying the severity of patients using specific tools such as prognostic indices.Objective: To assess the incidence of unfavorable outcomes in the severity of ICU patients before the pandemic period and after in patients without covid and with covid, respectively. Method: An ambispective casecontrol study was carried out, prospectively - control groups with data collection between 2018 and 2019 and retrospective - case groups with data collection between 2020 and 2022.The analyzed outcomes were death, acute kidney injury, and dialysis. Survival and mean survival time were estimated using the Kaplan-Meier estimator and compared using the log-rank test. The predictive capacity of scores in predicting unfavorable outcomes was evaluated by the Receiver Operating Curve (ROC) and estimated by the area under the curve (AUC). The significance level adopted was 5%. The research project was approved by the Research Ethics Committee of the Federal University of Sergipe, with a favorable opinion under numbers 2,830,187 and 5,144,304. Results: The sample consisted of 581 eligible patients for the study, with 180 (32.1%) patients diagnosed with COVID-19 and 381 (67.9%) patients without COVID-19. SAPS3 values on the first day (54.5 [41-65] vs 26 [15-34.5]; p<0.001) and at discharge (52.5 [45-62] vs 20 [10-32]; p<0.001); SOFA on the first day (8 [4-10.5] vs 4 [1-6]; p<0.001) and at discharge (7 [3-10] vs 1 [0-4]; p<0.001), and NAS on admission (89.7 [70.1-99.8] vs 48.1 [42.5-52.2]; p<0.001) and at discharge (97.2 [62-108.3] vs 49.7 [43.5-60]; p<0.001) were worse in patients with COVID-19. The average survival of patients with COVID-19 was 106 days, while those without COVID-19 were 120 days, which was statistically different (p<0.001). Conclusion: When analyzing the severity profile, clinical outcomes in patients admitted to intensive care units, patients diagnosed with COVID-19 had a higher risk of death, kidney injury, dialysis and greater nursing workload compared to patients without COVID-19.